Characterization of cakes produced with different legume aquafaba - Konal, Gozde; Dundar, Ayse Neslihan; Sahin, Oya Irmak; Parlak, Mahmut Ekrem; Saricaoglu, Furkan Turker (Elsevier, 2025)
This study investigates the potential of aquafaba, derived from various legumes including white chickpeas, black chickpeas, white beans, and red beans, as an egg substitute in cake production. Aquafaba samples were analyzed for physicochemical properties and functional characteristics at different pH levels. The results revealed that the foam and emulsion properties of all aquafaba samples at pH 3 were superior to those obtained at other pH values. Specifically, at pH 3, foam capacity values were approximately 238.74 f 28.54%, 231.25 f 26.52%, 237.50 f 17.68%, and 112.50 f 17.68% for aquafaba derived from white chickpeas, black chickpeas, white beans, and red beans, respectively. Aquafaba derived from white chickpeas demonstrated the highest foam stability at pH 3 (92.43 f 0.61%), followed by black chickpeas (86.96 f 3.30%). Similarly, emulsion capacity at pH 3 was highest for aquafaba derived from white chickpeas (41.14 f 11.73%), followed by black chickpeas (65.33 f 26.28%), white beans (28.94 f 37.69%), and red beans (49.65 f 9.57%). Emulsion stability was measured as 100% for aquafaba derived from white chickpeas, black chickpeas, and white beans at pH 3, with slightly lower values observed for aquafaba from red beans. Furthermore, aquafaba derived from different legumes exhibited varying protein contents at pH 3, ranging from 17.75 f 0.05% to 19.20 f 0.09%. Cake production with aquafaba as an egg substitute was conducted at pH 3, with analyses including moisture, ash, protein, fat, color, texture, specific volume, weight loss, and sensory evaluation. Results indicate the potential of aquafaba as a versatile egg substitute in cake formulations, with promising foam and emulsion properties, protein content, and sensory attributes.
Keywords: Legume; Aquafaba; Egg; Waste utilization; Cake; Foam; Emulsion